Developing measures to improve strength indices of supporting structures for head cars of diesel trains DR1A on the basis of experimental-and-theoretical works - Bondarev, O. M.; Gorobets, V. L.; Yagoda, D. O.; Bondarev, O. O. (Science and Transport Progress, 2014)
Purpose. The objective is to determine the stress-strain state of supporting structures of the head car body and the traction transmission unit, which can be created in the operation of emergency situations, and to develop the measures aimed at improving the stress-strain state of these elements. Methodology. In order to achieve this objective, in performing the work an experimental determination of efforts and stress levels in the most loaded elements of supporting structures as well as the traction transmission units was conducted; design models for the theoretical determination of stress and effort levels were developed. Findings. Based on the analysis of the calculation results the best options for the upgrades, which have been put into the basis of proposals aimed at improving the strength indices, were revealed. Originality. Based on the experimental and theoretical studies, scientific monitoring of development works on modernization and improvement of strength indices of supporting structures of head cars of diesel trains DR1A was performed. Practical value. The technical solution to the measures, which are to be carried out beyond the limits of assigned operation lifetime for diesel train of the series specified was developed and transferred to the Ukrzaliznytsia experts to introduce the proposed measures on improving the strength indices.